Development of Promotion Media for Training Services through Podcasts to Improve the Performance of Public Service Agency (BLU) Organizations at the Malahayati Maritime Polytechnic: Pengembangan Media Promosi Layanan Diklat melalui Podcast guna Meningkatkan Kinerja Organisasi Badan Layanan Umum (BLU) di Politeknik Pelayaran Malahayati - Laju, I Kadek; Kurniadi, Dedy; Nugraha, Yohanes; Syukri, Mohammad; Sultan, Sultan (SABIQ: Jurnal Sosial dan Bidang Pendidikan, 2025)
One of the strategic targets of the Malahayati Maritime Polytechnic in managing the Public Service Agency (BLU) is to keep up with the times by adopting relevant educational services as very important. The purpose of keeping up with the times in this modern era is to increase the number of participants interested in seafarer training by developing promotional media for training services. As an educational institution that focuses on maritime education services, maintaining and increasing the number of training participants is crucial. This study uses the Research and Development (R&D) method and the fundamental problems are examined using the SWOT analysis method. The results of this study are: 1) Transforming training services to improve organizational performance by developing promotional methods through the use of Podcast media; 2) Transformational leadership that focuses on creating positive change in the organization by inspiring and motivating team members or followers is very much needed; and 3) The provision of this Podcast space is also a media that is expected to be able to improve the quality of education with more up-to-date learning methods.